Do surveys (mis)lead? A note for practitioners. Issue 6 (18th August 2018) - Sushant,; Kaur, Sunpreet; Saigal, Sushil
ABSTRACT: Surveys are a widely used research method in development programmes to measure and assess the needs, priorities, and severity of problems. Using surveys as a tool to gauge developmental needs, we assessed the effect of monetary contribution, degree of participation, and seasonality on beneficiaries' demands. It was found that a lack of procedural engagement with the target audience leads to unrealistic demands, which in turn negatively impact the development programme. This practical note offers guidelines to practitioners and researchers that they may adopt before undertaking large-scale surveys.